Synthesis of Mantiq and Kalam: A Study of the Theological Reasoning of the Millennial Muslim Generation - Didin Hidayat; Nazla Fahira Balfas; Rehan Hamaludin; Samsul Rijal; Siti Aditta (Al-Abqori: Journal of Islamic Thought Studies, 2026)
Theology and logic are two branches of science that have a central role in the development of theological reasoning in the Islamic tradition. Theology focuses on the discussion of Islamic faith and beliefs using rational arguments to strengthen and maintain faith, while logic is the science of logic that regulates correct and systematic ways of thinking in order to produce valid conclusions. The synthesis between logic and theology is very relevant in the context of the development of the thinking of the millennial generation of Muslims who live in the digital and globalization era, where intellectual and social challenges are increasingly complex. This study uses a qualitative method with a literature study approach to examine how the principles of logic (logic) are applied in theology in order to build critical, rational, and adaptive theological reasoning to the dynamics of the times. This study examines the existence of logic as a basis for thinking, the implications of bayani, burhani, and irfani reasoning in Islamic science, and the role of theology in facing contemporary theological challenges. The results of the study show that the synthesis of logic and theology not only strengthens faith rationally, but also equips the millennial generation of Muslims with critical and dialogical thinking skills that are able to answer religious and social problems scientifically. Therefore, strengthening theological education based on logic is a strategic need in building the theological reasoning of the millennial generation that is relevant and constructive in facing the industrial revolution and current global challenges.